KEDUDUDKAN HUKUM ANAK LUAR KAWIN MENURUT UNDANG UNDANG PERKAWINAN NO 1 TAHUN 1974 PASCA LAHIRNYA PUTUSAN MK RI NO 46/PUU-VII/2010 TERHADAP IBU KANDUNG DAN AYAH BIOLOGIS - MOHAMAD ROULLY PARSAULIAN LUBIS (PREMISE LAW JURNAL, 2016)
An illegitimate child’s status is the result of illegal marriage. Concerning his civil right, development, caring, and subsistence, it is basically the liability of his biological mother as it is stipulated in the Marriage Law No. 1/1974. He only has civil relation with his biological mother and with her relatives. After the issuance of the Supreme Court’s Ruling No. 46/PUU-VII/2010 which has amended Article 43 of the Marriage Law, states that an illegitimate child, who used to have the relation with his biological mother, not only has the relation with his biological mother but also with his biological father. This legal protection and legal certainty can be taken by filing a complaint to the Court and giving evidence by carrying out DNA test by medical forensic team. In this case, it must be through legal procedure through the court’s judge who orders the evidence by DNA test. Keywords: Illegitimate Child, the Supreme Court’s Ruling, Biological Father, Biological Mother